Observation of Hypotrichidium¬¬¬¬ tetranucleatum sp.nov. (Ciliophora: Strichotrichida) from Aurangabad, M.S., India - More B.V, Deshmukh N.Z*, Nikam S.V and (Recent Research in Science and Technology, 2011)
A new species Hypotrichidium tetranucleatum sp.nov. is observed belonging to the genus Hypotrichidium from the fresh water body in Aurangabad, Maharashtra, India. This is the free living form of ciliate protozoa found in water. The new species is characterized by elongate body shape with Adoral zone of membranelle running one-third the body length, four macronuclei, four micronuclei and one contractile vacuole located at the posterior left of the body.